Systematic modulation of charge and spin in graphene nanoribbons on MgO - Amelia Domínguez-Celorrio; Leonard Edens; Sofía Sanz; Manuel Vilas-Varela; Jose Martinez-Castro; Diego Peña; Véronique Langlais; Thomas Frederiksen; José I. Pascual; David Serrate (Nature Communications)
Abstract In order to take full advantage of graphene nanostructures in quantum technologies, their charge and spin state must be precisely controlled. Graphene quantum dots require external gating potentials to tune their ground state. Here, we show systematic manipulation of the electron occupation in graphene nanoribbons lying on MgO layers grown on Ag(001). Owing to the efficient electronic decoupling character of MgO, and the electropositive nature of the substrate, the ribbons host an integer number of electrons that depend on their length and shape. This results in the alternation between a non-magnetic closed-shell state and an open-shell paramagnetic system for even and odd electron occupations respectively. For the odd case, we find a narrow Coulomb correlation gap, which is the smoking gun of its spin-½ state. Comparisons of scanning tunnelling microscopy data with mean-field Hubbard simulations confirm the discretization of the ribbons’ electronic states and charge excess of up to 19 electrons per ribbon.